MODEL BIMBINGAN KESEHATAN MENTAL UNTUK PARA SANTRI PONDOK PESANTREN SYAFI’IYAH CISAMBENG MAJALENGKA - Yedi Supriadi (Pascasarjana IAIN Syekh Nurjati Cirebon, 2017)
The goal of the research are to describe the development of the mental health for young students at the boarding school in the islamic school of Syafi'iyyah in Cisambeng city of Palasah-Majalengka regency. Development of mental health in question is with the planting of character and morals and a healthy mental approach to the students through some methode is called “shuhbah” (friendship) for the purpose of mental development can be achieved easily, accurately, effectively and efficiently. The method of the research are using descriptive method with collecting some information, by techniques gained through observation, interviews, questionnaires and documentation study. Data retrieval is derived from respondents who are seen mental health problems with a purposive sampling technique that aims to find out what the problem occurs in teenagers these students then how after he followed the guidance of mental health at boarding Syafi'iyyah Cisambeng approach by “shuhbah” (friendship). Islamic conseling emphasizes spiritual solutions based on love and fear of Allah and the duty of fulfil our responsibility as the servants of Allah on this earth.The results of the research illustrate that the application of mental health counseling with shuhbah (friendship) perceived benefit to the students who participated in mental health counseling because after being interviewed and completed questionnaires the students who have experienced problems of mental disorders (misconduct) after obtaining calculated the mean category average high.Based on the recognition of the students, they are feel much better after attending mental health training activities in Pondok Pesantren Syafi'iyyah Cisambeng guided by Mas Nawawi (Ustd.Muhamad Nawawi Fathulloh, M.Pd.I). Thus the results of this study presented a picture of the actual conditions in the field as the information and report the study authors. Keywords: Model Guidance, Mental Health, and Pupils